CODEL: phase III study of RT, RT + TMZ, or TMZ for newly diagnosed 1p/19q codeleted oligodendroglioma. Analysis from the initial study design - Jaeckle, Kurt A.; Ballman, Karla V; van den Bent, Martin; Giannini, Caterina; Galanis, Evanthia; Brown, Paul D; Jenkins, Robert B; Cairncross, J Gregory; Wick, Wolfgang; Weller, Michael; Aldape, Kenneth D; Dixon, Jesse G; et al. (Neuro-Oncology, 2021)
We report the analysis involving patients treated on the initial CODEL design.Adults (>18) with newly diagnosed 1p/19q World Health Organization (WHO) grade III oligodendroglioma were randomized to radiotherapy (RT; 5940 centigray ) alone (arm A); RT with concomitant and adjuvant temozolomide (TMZ) (arm B); or TMZ alone (arm C). Primary endpoint was overall survival (OS), arm A versus B. Secondary comparisons were performed for OS and progression-free survival (PFS), comparing pooled RT arms versus TMZ-alone arm.Thirty-six patients were randomized equally. At median follow-up of 7.5 years, 83.3% (10/12) TMZ-alone patients progressed, versus 37.5% (9/24) on the RT arms. PFS was significantly shorter in TMZ-alone patients compared with RT patients (hazard ratio [HR] = 3.12; 95% CI: 1.26, 7.69; P = 0.014). Death from disease progression occurred in 3/12 (25%) of TMZ-alone patients and 4/24 (16.7%) on the RT arms. OS did not statistically differ between arms (comparison underpowered). After adjustment for isocitrate dehydrogenase (IDH) status (mutated/wildtype) in a Cox regression model utilizing IDH and RT treatment status as covariables (arm C vs pooled arms A + B), PFS remained shorter for patients not receiving RT (HR = 3.33; 95% CI: 1.31, 8.45; P = 0.011), but not OS ((HR = 2.78; 95% CI: 0.58, 13.22, P = 0.20). Grade 3+ adverse events occurred in 25%, 42%, and 33% of patients (arms A, B, and C). There were no differences between arms in neurocognitive decline comparing baseline to 3 months.TMZ-alone patients experienced significantly shorter PFS than patients treated on the RT arms. The ongoing CODEL trial has been redesigned to compare RT + PCV versus RT + TMZ.
Published: 17 July 2020
Gesehen am 13.07.2021